Untitled, watercolor on paper painting by Fernand Léger, 1921, Honolulu... - Fernand Léger (Wikimedia Commons, 1921)
Notice iconographique issue de Wikimedia Commons. Titre: Untitled, watercolor on paper painting by Fernand Léger, 1921, Honolulu Museum of Art. Untitled, watercolor on paper painting by Fernand Léger, 1921, Honolulu Museum of Art.
Droits : Licence Public domain via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons; Peintures